2013
DOI: 10.7566/jpsj.82.044707
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Entropy \(\ln\sqrt{2}\) by Ordering in Two-Channel Kondo Lattice

Abstract: Peculiar property of electronic order is clarified for the two-channel Kondo lattice. With two conduction electrons per site, the order parameter is a composite quantity involving both local and itinerant degrees of freedom. In contrast to the ordinary Kondo lattice, a heavy electron band is absent above the transition temperature, but is rapidly formed below it. The change of entropy associated with the ordering is found to be close to ln √ 2 per site. This entropy corresponds to the residual entropy in a two… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 30 publications
3
58
0
Order By: Relevance
“…3(f)); however, we did not find any evidence for such split features below the Fermi level. Moreover, the wave vector of the hole pocket is smaller than the value deduced in previous spectroscopic studies181933, further supporting the irrelevance. (2) Our data support that the energy gap is formed at the Fermi level upon the transition, and the ‘M-shaped’ band does not cross the Fermi level below T HO .…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…3(f)); however, we did not find any evidence for such split features below the Fermi level. Moreover, the wave vector of the hole pocket is smaller than the value deduced in previous spectroscopic studies181933, further supporting the irrelevance. (2) Our data support that the energy gap is formed at the Fermi level upon the transition, and the ‘M-shaped’ band does not cross the Fermi level below T HO .…”
Section: Discussionsupporting
confidence: 57%
“…(4) There is no conclusive evidence for any bulk hole-like band being involved in the hybridization. One possible reconciliation is that another hole pocket remains undetected in ultrahigh-resolution ARPES owing to the matrix-element effect; another interesting possibility is that the ‘M-shaped’ band is formed by a mechanism unique to a two-channel Kondo lattice33; this model does not necessarily require the existence of a hole pocket in the disordered state.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we first briefly summarize the known properties of the TCKL. According to the previous studies [40,42], the system shows a non-Fermi-liquid behavior in the disordered phase even at low temperatures. This is due to the residual entropy that cannot be removed by the Kondo effect in the two-channel case.…”
Section: Two-channel Kondo Lattice and Composite Ordersmentioning
confidence: 73%
“…Thus, the effective model for the channel order with z is given by the following one-body hybridization model [42,49]:…”
Section: A Derivation Of One-body Hamiltonian For Composite Pairing mentioning
confidence: 99%
“…In the last decade, the lattice version of the two-channel Kondo problem has also been studied theoretically [9], and in particular, by means of the so-called dynamical mean-field theory, it is found that it exhibits a variety of long-range orderings [10,11]. The analytic expressions of T dependence are obtained as…”
Section: C(t )/T χ(T ) ∝ − Ln(t /T 2k ) ρ(Tmentioning
confidence: 99%